Signtastic / Muhammad Idil Hakim Shahrom ... [et al.] - Shahrom, Muhammad Idil Hakim; Ahmed Suhaimi, Muhaimyn; Roslizan, Nur Amalia Amira; Azmi, Anis Suraya; Ibahrom, Nur Nabilah
Due to a lack of awareness on how to communicate with a deaf person and a lack of knowledge of sign language, the number of people experiencing difficulty speaking with a deaf person has increased day by day. According to a new estimate from the World Health organisation (WHO), one in every four people, or roughly 2.5 billion people, will have mild-to-profound hearing loss by 2050. At least 700 million individuals are expected to suffer from debilitating hearing loss and require ear and hearing care. Damage to the inner ear is one of the most common causes of hearing loss, and some people are born deaf. Thus, in New Product Development (NPD), we came out with a solution to produce a sign language app called Signtastic. We think that knowing sign language assists you to communicate with those who are deaf, hard of hearing, or deaf individuals. People in the community will find it simpler to communicate with a deaf person using Signtastic. This application also enables users to learn the whole range of sign language, including alphabets, facial emotions, and body postures. We may use this software to handle issues like miscommunication and misunderstanding that might arise between hearing and deaf persons. There is so much uniqueness in this software that it even includes a scanning capability that allows it to precisely recognise images and deliver sign language translation. Signtastic is a programme that translates English texts into sign language. This software includes a variety of sign languages, such as British Sign Language (BSL), American Sign Language (ASL), Malaysian Sign Language (MSL), and others. As a result, users may utilise Signtastic to learn sign language specific to their respective nations or areas.